Pediatricians, Well-Baby Visits, and Video Intervention Therapy: Feasibility of a Video-Feedback Infant Mental Health Support Intervention in a Pediatric Primary Health Care Setting - Facchini, Sergio; Martin, Valentina; Downing, George (Frontiers in Psychology, 2016)
This case series study evaluated the feasibility and acceptability of a behavioral/cognitive psychological intervention in a pediatric primary health care setting during standard well-baby visits. The aim of the intervention was to support caregivers’ sensitivity and mentalization in order to promote infant mental health (IMH). Four neonates from birth to 8 months were consecutively enrolled to test a short video-feedback intervention (Primary Care – Video Intervention Therapy, an adaptation of George Downing’s Video Intervention Therapy to primary care) conducted by a pediatrician. The 5 min interaction recording and the video-feedback session were performed during the same well-baby visit and in the same pediatrician’s office where the physical examination was conducted. During the study period, six video-feedback sessions were performed for each baby at different ages (1, 2, 3, 4, 6, 8 months). A series of different interactional situations were filmed and discussed: touch, cry, affective matching, descriptive language, feeding, separation and autonomy. The intervention was easily accepted and much appreciated by all four families enrolled. This study aimed to answer a dilemma which pediatric providers generally face: if the provider wishes to respond not only to physical but also IMH issues, how on a practical level can this be done? This case series study indicates that Primary Care – Video Intervention Therapy can be a promising new tool for such a purpose.